Histo-architectural changes of intestinal morphology in Zebra fish (Danio rerio) exposed to Sumithion (Research in Agriculture Livestock and Fisheries, 2015)
Organophosphorous pesticide sumithion, the O, O Dimethyl O- (3-methyl-4-nitrophenyl), is a widely used pesticide in agricultural land and in aquaculture to control some harmful pests. A study was conducted in laboratory condition with aquaria (36 inch × 10 inch × 12 inch) to evaluate the effects of sumithion on histo-architecture of intestine in zebrafish (Danio rerio). The experiment was carried out with three treatments (T1: 0.5 ppm, T2: 1.0 ppm, T3: 2.0 ppm) and a control (T0: 0ppm), each having three replications. Zebra fishes (Danio rerio) (4±1cm and 0.9±0.2g) were stocked for the experiment and sacrificed after 7 days of exposure of sumithion. During the study period, the temperature was almost constant (21- 22OC) but dissolved oxygen, pH and total alkalinity values were tended to decrease with the increase in concentrations of test chemicals. The histo-architectural changes in intestine suggested that the intestinal epithelial cells, lumen, villi and intestinal folding were varied significantly (P